CHARACTERISTICS OF SELF-CITATIONS IN JOURNAL OF NATURAL RUBBER RESEARCH 1988- 1997: A TEN-YEAR BIBLIOMETRIC STUDY - Tiew, W. S. (Malaysian Journal of Library and Information Science, 2000)
Analyses the extent of journal self-citation and author self-citation in the research articles and short communications published in Journal of Natural Rubber Research during 1988 to 1997. Results show that 53% of articles contained journal self-citations; the rate of journal self-citations per article ranges between 1 to 12; a high percentage of authors (61.4%) contributing articles to the journal cited themselves; a tendency is noticed for authors affiliated to the institution publishing the journal to cite the journal; the highest self-citing author is A. D. Roberts.